Development of loop-mediated isothermal amplification for a simple and rapid detection of leptospiral DNA in human samples - Othman, Shuhaidah (2018)
Leptospirosis is a zoonotic disease caused by bacteria of genus Leptospira that affects both humans and animals worldwide. Early detection of leptospirosis is crucial to provide appropriate treatment and control the progression of the disease to a severe state. Hence, this study aims to develop a simple and rapid LAMP system for detection of Leptospira in suspected leptospirosis patients. LAMP primer set was specifically designed to target the secY gene of Leptospira. Recombinant plasmid containing the target gene was constructed and used as template in optimization procedure. Optimization of the LAMP reaction was done on the incubation temperature and reagents concentration. It was found that the designed LAMP primer set works best at 65°C and optimum concentration of betaine and MgSO4 was optimized at 0.4 M and 8 mM respectively. Sensitivity of the LAMP system was assessed based on the lower limit of detection using serially diluted genomic DNA of Leptospira interrogans serovar Pomona. The results showed that as low as 2 x 104 copies of genomic DNA per reaction (equivalent to 0.1 ng) could be detected within 40 min of reaction. The specificity of the system was tested by using DNA extracted from 15 leptospiral and nine non-leptospiral bacteria. None of the non-leptospiral DNA was amplified in the reaction indicating a highly specific system. Spiking assay was performed to mimic the clinical situation for determining the clinical sensitivity of the LAMP system. Pure culture of L. interrogans serovar Pomona were spiked into blood and urine samples donated by healthy donors. In spiked blood samples, 1 x 102 leptospires/ml was found to be the detection limit. Two methods of DNA isolation from spiked urine samples; column purification and direct boiling were performed to compare the efficiency. It was observed that samples from column purification results in higher LAMP amplification rate and more sensitive compared to direct boiling where the detection limit was found to be 1 x 102 leptospires/ml and 1 x 103 leptospires/ml respectively. As a proof-of-concept, the optimized LAMP system was performed on samples of blood and urine from suspected leptospirosis patients. The results were compared with conventional secY polymerase chain reaction (PCR). In 30 min LAMP reaction, 28 of 69 blood samples collected during admission was found to be positive. Of these, only 26 samples were able to be detected using PCR. As for admission urine samples, of 34 tested, 16 were positive by LAMP against 14 for PCR. These positive urine samples include those collected as early as on the third day of clinical symptoms onset suggesting urine could be use as well for diagnosis of leptospirosis apart of using blood samples during admission. In conclusion, the developed LAMP system can serve as an alternative rapid diagnosis of leptospirosis considering its robustness, sensitivity and specificity as demonstrated in this study.